Research on green total factor productivity of China’s mining industry - Li, Yu-Yang; Meng, Xiao-Li; Chen, Bo (Frontiers in Earth Science, 2025)
As China transitions towards a circular, green, and efficient economy, the mining industry, as a crucial pillar of national economic growth, faces dual challenges of resource efficiency and environmental governance. Against this backdrop, this study emphasizes the evaluation of green total factor productivity (GTFP) in China’s mining industry, aiming to provide scientific insights to environmental pollution. To overcome the limitations of traditional radial and non-radial Data Envelopment Analysis (DEA) models, this study adopts the SBM model and incorporates the Malmquist-Luenberger (ML) index to analyze GTFP from both static and dynamic perspectives across 31 provinces in China from 2005 to 2021, and provides specific suggestions.